Gingival abrasion and recession in manual and oscillating–rotating power brush users. Issue 4 (28th May 2014) - Rosema, NAM; Adam, R; Grender, JM; Van der Sluijs, E; Supranoto, SC; Van der Weijden, GA
Abstract Objective To assess gingival recession (GR) in manual and power toothbrush users and evaluate the relationship between GR and gingival abrasion scores (GA). Methods This was an observational (cross‐sectional), single‐centre, examiner‐blind study involving a single‐brushing exercise, with 181 young adult participants: 90 manual brush users and 91 oscillating–rotating power brush users. Participants were assessed for GR and GA as primary response variables. Secondary response variables were the level of gingival inflammation, plaque score reduction and brushing duration. Pearson correlation was used to describe the relationship between number of recession sites and number of abrasions. Prebrushing (baseline) and post‐brushing GA and plaque scores were assessed and differences analysed using paired tests. Two‐sample t‐test was used to analyse group differences; ancova was used for analyses of post‐brushing changes with baseline as covariate. Results Overall, 97.8% of the study population had at least one site of ≥1 mm of gingival recession. For the manual group, this percentage was 98.9%, and for the power group, this percentage was 96.7% (P = 0.621). Post‐brushing, the power group showed a significantly smaller GA increase than the manual group (P = 0.004); however, there was no significant correlation between number of recession sites and number of abrasions for either group (P ≥ 0.327). Conclusions Little gingival recession was observed in either toothbrush user group; the observed GR levels were comparable. Lower post‐brushing gingival abrasion levels were seen in the power group. There was no correlation between gingival abrasion as a result of brushing and the observed gingival recession following use of either toothbrush.